Effect of Zn Content on Physicochemical Characteristics, Photocatalytic Activity and Antibacterial Activity of Hydrothermally Synthesized Zn-Doped Hydroxyapatite - Fauziyyah, Anas Zahra; Sagadevan, Suresh; Fatimah, Is (Trends in Sciences, 2025)
This study explores the effect of zinc (Zn) content on the physicochemical characteristics, photocatalytic activity, and antibacterial activity of hydrothermally synthesized hydroxyapatite (HAp). Zinc doped HAp (Zn-HAp) was synthesized with varying Zn content of 1, 2 and 5 wt%, and characterized using XRD, FTIR, UV-Vis DRS, TEM, and zeta potential analysis. Characterization results showed that Zn was successfully dopped into the HAp structure without forming its own ZnO phase, with a decrease in crystallite size and band gap. Photocatalytic activity test was conducted by degradation of tetracycline (TC) antibiotic using UV light. The results show that Zn-HAp has higher photocatalytic activity than pure HAp, with the highest degradation efficiency of 90.48% obtained at 1Zn-HAp. The photocatalytic activity increased as the band gap decreased, which was facilitated by Zn doping. In addition, antibacterial tests against Escherichia coli and Staphylococcus aureus showed that Zn-HAp had a larger inhibition zone than pure HAp, indicating an increase in antibacterial activity, especially at higher Zn concentrations. HIGHLIGHTS Zinc-doped hydroxyapatite with a varied zinc have been synthesized by hydrothermal method. Increasing Zn content in Zn-HAp affects to reduce crystallite size and band gap energies The reduced band gap energy leads to the enhanced photocatalytic activity. Zn-HAp samples show the higher tetracycline photocatalytic activity compared to HAp at 90.84 %. Zn-HAp samples showed good antibacterial activity against Eschericia coli and Staphylococcus aureus. GRAPHICAL ABSTRACT